Health-wellness resources on Canadian immigrant service provider organizations' websites: A content, navigability, usability, and credibility analysis towards service & asset mapping - Ayisha Khalid; Nashit Chowdhury; Mohammad ZI Chowdhury; Tanvir C Turin (Elsevier, 2022)
Background: Immigrant service provider organizations (SPOs) are often immigrants' first point of contact to Canadian systems, such as job, education, health and social care, and housing. Prior research emphasizes the health literacy potential of websites as information infrastructures that can reduce information poverty and improve health outcomes. Yet, whether health-wellness resources are present on immigrant SPOs' websites in a user-friendly manner remains unexplored. Methods: We identified the presence of health-wellness resources on SPOs' websites and analyzed those contents to understand their typology. We also ascertained the navigability, usability, and credibility of those websites regarding the health-wellness resources. Results: Among the 1453 SPO websites identified, only 289 (35.9%) had health-wellness information in their web-contents. Of the websites with health-wellness contents, "lifestyle and wellness resources" were present on 86.5% and "healthcare system resources" were present on 80.6% of the websites. Regarding "navigability", zero to two mouse clicks were required to access health-wellness resources on 94.8% of the websites; however, more than one language option was very limited, available on less than a quarter of websites. Conclusions: As immigrants continue to seek information online, immigrant SPOs' websites hold value in increasing the health literacy and health-wellness of immigrants. This research assessed the current state of immigrant SPOs' websites as information infrastructures and reveals areas for improvement. We recommend SPOs add resources for obtaining healthcare card, accessing primary care, sexual and reproductive, parenting, senior's health, mental wellbeing, and women's health information to their websites. We also recommend websites accommodate ethnic language option to improve navigability for immigrants.